2016
DOI: 10.4103/1793-5482.175636
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous closure of posttraumatic high-flow carotid-cavernous fistula following cerebral angiography

Abstract: Traumatic carotid-cavernous fistula (TCCF) is a direct communication between cavernous portion of the internal carotid artery (ICA) and cavernous sinus due to tear in ICA. Most of the cases are treated by endovascular embolization. Spontaneous resolution of high-flow TCCFs is extremely rare. We report a case of posttraumatic, direct, high-flow carotid cavernous fistula (Barrow type A) that resolved spontaneously after cerebral angiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 9 publications
(12 reference statements)
0
10
0
Order By: Relevance
“…extreme proptosis, chemosis, and/or pain) representing a process of acute thrombosis as found in our series (cases 2, 3, and 4) and many other case reports. 12,13,16,[33][34][35][36]40,41 The ophthalmic vein became intensely distended with venous blood received reversely from the cavernous sinus, which corresponded with a sudden reduction of the flow rate, resulting in a thrombosed vein. 49 Similarly, spontaneous occlusion of a traumatic CCF immediately following orbital venography was reported by Nishijima et al 24 The authors proposed that a possible mechanism responsible for spontaneous closure of the fistula was a temporary reduction in the pressure gradient between the cavernous sinus and the ICA, leading to stasis of the blood flow causing formation of a thrombus within the cavernous sinus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…extreme proptosis, chemosis, and/or pain) representing a process of acute thrombosis as found in our series (cases 2, 3, and 4) and many other case reports. 12,13,16,[33][34][35][36]40,41 The ophthalmic vein became intensely distended with venous blood received reversely from the cavernous sinus, which corresponded with a sudden reduction of the flow rate, resulting in a thrombosed vein. 49 Similarly, spontaneous occlusion of a traumatic CCF immediately following orbital venography was reported by Nishijima et al 24 The authors proposed that a possible mechanism responsible for spontaneous closure of the fistula was a temporary reduction in the pressure gradient between the cavernous sinus and the ICA, leading to stasis of the blood flow causing formation of a thrombus within the cavernous sinus.…”
Section: Discussionmentioning
confidence: 99%
“…Absence of posterior drainage and single venous drainage have been proposed to play a role in spontaneous occlusion of the fistula. 6,40 Nishijima et al 24 reviewed six cases of spontaneous occlusion of traumatic CCF verified by angiography and found that the venous drainage was either anterior or posterior drainage. However, our review found combined anterior, posterior/inferior drainages, and/or cortical venous reflux in nearly 30% of all fistulas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In rare instances, treatment requires direct endovascular access of the superior ophthalmic vein, using an upper eyelid cut-down technique. Few documented cases of spontaneous resolution of type A fistulas are reported in the literature, varying anywhere from a few days to 6 months [9,10,11,12,13,14,15,16]. The exact mechanism of this process is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Trauma is common to most medical conditions, and it follows orthognathic, plastic, and minor surgeries, such as phinoplasty, [6] Ext.Ethmoidsurgery, [7] Biopsy, [8] LeFort I osteotomy. [9] These cases are defined as traumatic, with males outnumbering females at a ratio of 2:1.…”
Section: Discussionmentioning
confidence: 99%